An insight On The Contemporary Islamic Art Of Brunei From 1984 To 2019 - Pg Aliudin, Pg Mohd Rahiman; Rui Oliveira Lopes; Maslin bin Jukim/Jukin (LPPM Universitas Gunung Rinjani, 2024)
As one of the Muslim-majority countries in Southeast Asia, Brunei Darussalam is not new when it comes to the production of contemporary Islamic artworks, with its local artists regularly showcasing their work in both local and international art exhibitions. However, it is notable that comprehensive academic investigations focusing on the field of Islamic art in Brunei remain noticeably absent. As a result, this study aims to address this gap by examining contemporary Islamic art in Brunei from 1984 to 2019, produced by its local Muslim artists. Employing a formal analysis approach, this study focuses on three primary aspects of the artworks to obtain an insight into the trends of the production: (1) date of production, (2) art media, and (3) artistic styles. A total of 384 visual artworks including drawings, paintings, sculptures, mixed media and installations were analysed. The year 1984 is selected as this study’s starting point due to its historical significance in Brunei’s trajectory, coinciding with its Independence Day. Since then, the country has experienced notable developments in its governance, economic stability, administrative reforms, religious institutions, educational enhancements, and, consequently, its art practices.